Impact of vaccination with different types of rotavirus vaccines on the incidence of intussusception: a randomized controlled meta-analysis - Guoyong Wang; Guoyong Wang; Guoyong Wang; Kaijun Zhang; Kaijun Zhang; Kaijun Zhang; Rensen Zhang; Rensen Zhang; Xiangru Kong; Xiangru Kong; Chunbao Guo; Chunbao Guo; et al. (Frontiers Media S.A., 2023)
BackgroundIntussusception is a prevalent pediatric issue causing acute abdominal pain, with potential links to rotavirus vaccines. The variety of these vaccines has grown in recent years. This meta-analysis study aims to evaluate the impact of various rotavirus vaccines on intussusception incidence.MethodsWe executed a thorough search across databases like PubMed, Cochrane Library, Embase, and Web of Science, leading to the selection of 15 credible randomized controlled trials (RCTs) that encompass various types of rotavirus vaccines. From each study, we extracted essential details such as vaccine types and intussusception occurrences. We assessed the risk of bias using the Cochrane Collaboration's tool, conducted statistical analysis with R (version 4.2.3), determined relative risk (RR) using a random effects model, and performed a subgroup analysis for vaccines of differing brands and types.ResultsWe included 15 randomized controlled studies from various countries. While intussusception incidence differed between vaccinated and control groups, this difference was not statistically significant. The overall risk ratio (RR), calculated using a random effects model, was 0.81, with a 95% confidence interval of [0.53, 1.23]. This crossing 1 shows that vaccination didn't notably change disease risk. Additionally, the 0% group heterogeneity suggests consistency across studies, strengthening our conclusions. Subgroup analysis for different vaccine brands and types (RV1 (Rotarix, Rotavac, RV3-BB), RV3 (LLR3), RV5 (RotasiiL, RotaTeq), and RV6) showed no significant variation in intussusception incidence. Despite variations in RR among subgroups, these differences were not statistically significant (P > 0.05).ConclusionsOur study indicates that rotavirus vaccination does not significantly increase the incidence of intussusception. Despite varying impacts across different vaccine brands and types, these variations are insignificant. Given the substantial benefits outweighing the risks, promoting the use of newly developed rotavirus vaccines remains highly valuable.Systematic Review Registrationwww.crd.york.ac.uk/prospero/, Identifier CRD42023425279.